2006
DOI: 10.1152/ajpheart.00479.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by postconditioning in conscious rats is limited to coronary occlusions <45 min

Abstract: tection by postconditioning in conscious rats is limited to coronary occlusions Ͻ45 min. Am J Physiol Heart Circ Physiol 291: H2308-H2317, 2006. First published June 30, 2006 doi:10.1152 doi:10. /ajpheart.00479.2006 Brief episodes of ischemia and reperfusion after a lethal ischemic insult confer cardioprotection, a phenomenon termed "ischemic postconditioning." However, all studies reported to date have been conducted in open-chest animal models. We sought to determine whether postconditioning occurs in consc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 32 publications
(54 reference statements)
6
49
0
3
Order By: Relevance
“…33,34 In addition, the effect of ischemic preconditioning and postconditioning is diminished with longer duration of ischemia, at least in the experimental setting. 6,7 Thus, the association between protection against reperfusion injury and system delay/duration of ischemia may be true with different cardioprotective strategies. The reason for the loss of cardioprotection with a longer duration of ischemia is not fully elucidated but may be related to that interventions generally are most effective in the first 2 to 3 hours after onset of ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 In addition, the effect of ischemic preconditioning and postconditioning is diminished with longer duration of ischemia, at least in the experimental setting. 6,7 Thus, the association between protection against reperfusion injury and system delay/duration of ischemia may be true with different cardioprotective strategies. The reason for the loss of cardioprotection with a longer duration of ischemia is not fully elucidated but may be related to that interventions generally are most effective in the first 2 to 3 hours after onset of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that the cardioprotective effect diminishes with long duration of ischemia. 6,7 Assessing duration of ischemia in clinical settings is problematic. Traditionally, the duration from symptom onset to balloon dilatation (treatment delay) is used…”
mentioning
confidence: 99%
“…In addition, these data underscore the important concept that, in the reperfusion era, final myocardial infarct size is the net result of a 2-component insult: the first (well-accepted) related to ischemia and the second (less known) secondary to reperfusion. [17][18][19] In the ensuing years since this first report by Zhao et al, 2 infarct size reduction with postconditioning has been described in most (but not all) experimental studies 20 and, despite the lack of complete consensus, [21][22][23][24] has emerged as a promising cardioprotective intervention. 20,[25][26][27][28] Moreover, the endogenous protection afforded by postconditioning is not limited to heart and can be applied to treat global or regional ischemia-reperfusion injury in other organs or tissues.…”
Section: Postconditioning: a Paradigm For The Treatment Of Lethal Repmentioning
confidence: 99%
“…The present data may also help to understand why, in pigs, postconditioning CAO30 with 3POC30 was not cardioprotective (29), while myocardial postconditioning in this species with the same stimulus after CAO75 was effective (17). Furthermore, it may help to explain why, in rats, in one study, 6POC10 afforded protection against CAO30 (34) but failed to protect against CAO60 (31).…”
Section: Importance Of Index Ischemia Durationmentioning
confidence: 99%